1973
DOI: 10.1111/j.1365-3032.1973.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel mimicry complex: beetles and flies

Abstract: SYNOPSIS A mimicry complex is described in which numerous taxa of beetles resemble flies. A probable explanation for the convergence on a common pattern is suggested, and the evolution of the complex is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 3 publications
0
25
0
2
Order By: Relevance
“…On the other hand, if there is a single resource needed by all, convergence to best utilize that resource may be the outcome (Abrams 1986, Fox andVasseur 2008). Evidence exists for both character displacement (divergence in trait values; e.g., Dayan andSimberloff 2005, Davies et al 2007), as well as convergence on similar trait values across different taxa in sympatry (Hespenheide 1973, Knouft 2003, Scheffer and van Nes 2006, Matocq and Murphy 2007, Kozak et al 2009, Mayfield and Levine 2010. For example, Davies et al (2007) found that sister species in the mammals with greater range overlap also have greater divergence in dentition, consistent with character displacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if there is a single resource needed by all, convergence to best utilize that resource may be the outcome (Abrams 1986, Fox andVasseur 2008). Evidence exists for both character displacement (divergence in trait values; e.g., Dayan andSimberloff 2005, Davies et al 2007), as well as convergence on similar trait values across different taxa in sympatry (Hespenheide 1973, Knouft 2003, Scheffer and van Nes 2006, Matocq and Murphy 2007, Kozak et al 2009, Mayfield and Levine 2010. For example, Davies et al (2007) found that sister species in the mammals with greater range overlap also have greater divergence in dentition, consistent with character displacement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Davies et al (2007) found that sister species in the mammals with greater range overlap also have greater divergence in dentition, consistent with character displacement. Alternatively, character convergence in response to competition has often been a stable outcome of models (e.g., Fox andVasseur 2008, Abrams 1986); convergence has been reported less frequently than divergence in empirical studies of competition (Hespenheide 1973, Knouft 2003, Scheffer and van Nes 2006, Matocq and Murphy 2007, Kozak et al 2009, Mayfield and Levine 2010. Adaptive phenotypic plasticity that reduces the strength of competition among interacting individuals Murphy 2003, Pfennig et al 2006) could result in trait convergence or divergence among species and could amplify or obscure phylogenetic signal in traits within communities, as traits may change in response to traits of neighboring species or individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several putatively mimetic color patterns are hypothesized to have evolved independently in multiple genera of New World Conoderinae, including: red-eyed flies (Hespenheide 1973, 1995; Figs 80, 87), dolichopodid flies of the genus Medetera Fischer von Waldheim, 1819 (Hespenheide 1995, 2005; Figs 94, 103), ants of the genus Zacryptocerus Kempf, 1973 (Hespenheide 1986), other species of ants (Hespenheide 1995; e.g. Figs 86, 93), bees (Hespenheide 1995; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All of the described and most of the observed undescribed species of Mnemynurus are members of the red-headed fly mimicry complex (Hespenheide 1973, 1995), and are most difficult to distinguish from the similarly patterned species of Hoplocopturus and the South American Balaninurus which also share the distinctive inverted U-shaped carina on the mesoventrite. See “Diagnosis” for Hoplocopturus above for more information on the separation of the genera.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Esta espécie é parte de um complexo envolvendo várias famílias de coleópteros (Anthribidae, Buprestidae, Cleridae, Curculionidae e Mordellidae) que são miméticos de dípteros, com colorido similar ao das famílias Tachinidae e Sarcophagidae (Hespenheide 1973;Valentine 1980).…”
unclassified